Angiofibroma Ekstranasofaring dari Hipofaring: Laporan Kasus yang Langka - Ratna Windyaningrum; Agung D Permana; Ongka M Saifuddin (Journal of Medicine and Health, 2022)
Angiofibroma is a histologically benign mesenchymal tumor though it is a potentially locally destructive fibrovascular tumor. Angiofibroma located in the head and neck comprises nasopharyngeal and extra-nasopharyngeal angiofibroma. The extra-nasopharyngeal angiofibroma itself is extremely rare. There was only two hypopharynx angiofibroma case in the recent literature. The aim of this report is to find out recurrence rate after mass extirpation surgery approach transcervical in this patient. A case of extra-nasopharyngeal angiofibroma from hypopharynx that arising from the left posterior pharyngeal wall was described in this report. A 32 years old man was admitted with 8 years history of lump located around the mouth and left side of the throat. There were no other significant complaints other than the lump itself. Histopathologic microscopic examination showed an angiofibroma. Angiofibroma is a benign and slow-growing mass. The conclusion is management of this case is the same as angiofibroma in general, by surgery approach. The mass was successfully removed surgically and thus far no recurrence or post-surgical complications were found one year after excision. Keywords: angiofibroma, extra-nasopharyngeal, hypopharynx, pharyngeal mass